Long-term function and optimization of mouse and human islet transplantation in the subcutaneous device-less site. Issue 6 (1st November 2016) - Pepper, Andrew R.; Bruni, Antonio; Pawlick, Rena L.; Gala-Lopez, Boris; Rafiei, Yasmin; Wink, John; Kin, Tatsuya; Shapiro, A. M. James
ABSTRACT: Clinical islet transplantation has routinely been demonstrated to be an efficacious means of restoring glycemic control in select patients with autoimmune diabetes. Notwithstanding marked progress and improvements, the broad-spectrum application of this treatment option is restricted by the complications associated with intrahepatic portal cellular infusion and the scarcity of human donor pancreata. Recent progress in stem cell biology has demonstrated that the potential to expand new β cells for clinical transplantation is now a reality. As such, research focus is being directed toward optimizing safe extrahepatic transplant sites to house future alternative β cell sources for clinical use. The present study expands on our previous development of a prevascularized subcutaneous device-less (DL) technique for cellular transplantation, by demonstrating long-term (>365 d) durable syngeneic murine islet graft function. Furthermore, histological analysis of tissue specimens collected immediately post-DL site creation and acutely post-human islet transplantation demonstrates that this technique results in close apposition of the neovascularized collagen to the transplanted cells without dead space, thereby avoiding hypoxic luminal dead-space. Murine islets transplanted into the DL site created by a larger luminal diameter (6-Fr.) (n = 11), reversed diabetes to the similar capacity as our standard DL method (5-Fr.)(n = 9). Furthermore, glucose tolerance testing did not differ between these 2 transplant groups (p > 0 .05). Taken together, this further refinement of the DL transplant approach facilitates a simplistic means of islet infusion, increases the transplant volume capacity and may provide an effective microenvironment to house future alternative β cell sources.